Community Service on Implementing Learning Media as Support Technology for Neurodivergent Children Community in Surabaya - Melvie Paramitha; Yulius Hari; Minny Elisa Yanggah; Chitra Santi (Asia Pacific Journal of Management and Education (APJME), 2024)
Neurodivergent children may present with conditions such as autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), dyslexia, or other learning differences. These children often face challenges in communication, social interaction, and academic performance, necessitating tailored support within educational settings. This community service program partners with ELMO, a community for neurodivergent children. The program's goals are twofold: to develop assistive learning media in the form of eLearning modules, and to facilitate technology transfer to ensure its sustainability. The Asset Based Community Development (ABCD) technique guides the program's methodology. Information gathering utilizes questionnaires and focus group discussions to tailor the program to the specific needs of neurodivergent students. The results have demonstrated a positive impact, satisfying both our partner organization and the parents of neurodivergent children who can now track their children's progress more effectively. The positive impact on learning and parental tracking highlights the potential of such collaborations to improve educational equity for neurodivergent students. Future efforts can focus on expanding the modules and promoting wider adoption to reach more children.